Handbook on teaching and learning in political science and international relations - Ishiyama, John T, 1960-; Miller, William J, 1984-; Simon, Eszter (Edward Elgar Publishing, 2015)
With a focus on providing concrete teaching strategies for scholars, the Handbook on Teaching and Learning in Political Science and International Relations blends both theory and practice in an accessible and clear manner. In an effort to help faculty excel as classroom teachers, the expert contributors offer representation from various types of institutions located throughout the world. Split into three distinct parts, this book discusses: curriculum and course design, teaching subject areas, in class teaching techniques. This important Handbook is an essential guide for anyone looking to teach political science and international relations at the university level